Morphology, Anatomy, And Structure of Macroalgae Communities in Coastal Waters of Meras Village - Kamalirang, Deo C.; Kepel, DEA, Rene Ch.; Rembet, Unstain N. W. J.; Wantasen, Adnan S.; Mantiri, Rose O. S. E.; Sangari, Joudy R. R. (Jurnal Ilmiah PLATAX, 2025)
Macroalgae are the main producers of oxygen and organic matter in coastal environments as a result of their photosynthetic activity, and together with phytoplankton form the basis of aquatic food webs. This research method uses the Line Transect method with a quadratic sampling technique. Data collection was carried out by placing 3 transect lines 50 m long, drawn perpendicularly from the beach towards the sea, with the assumption that the distribution of the community was even. The distance between transects is 30 m with a square distance of 5 m. The square size used for data collection is 1 x 1 m². The results of this research obtained 12 species consisting of 3 species of Rhodophyceae, 4 species of Phaeophyceae, and 5 species of Ulvophyceae. The distribution species density index is 5 individuals/m2, the diversity index is 1.7716, the species evenness index is 0.7129, the species richness index is 2.1983, and the species dominance index is 0.2310. Key words: Macroalgae, Morphology, Anatomy, Community structure, Meras. Abstrak Makroalga adalah produsen utama oksigen dan bahan organik di lingkungan pesisir sebagai akibat dari aktivitas fotosintesisnya, dan bersama-sama dengan fitoplankton membentuk dasar jaring makanan perairan. Metode penelitian ini menggunakan metode Line Transect dengan teknik sampling kuadrat. Pengambilan data dilakukan dengan peletakan transek sebanyak 3 garis transek sepanjang 50 m, ditarik tegak lurus dari pantai ke arah laut dengan asumsi bahwa penyebaran komunitas merata. Jarak antar transek 30 m dengan jarak kuadrat yaitu 5 m. Ukuran kuadrat yang dipakai untuk pengambilan data berukuran 1 x 1 m². Hasil penelitian ini diperoleh 12 spesies yang terdiri dari 3 spesies Rhodophyceae, 4 Phaeophyceae, dan 5 spesies Ulvophyceae. Indeks kepadatan jenis sebar 5 individu/m2, indeks keanekaragaman sebesar 1,7716, indeks kemerataan jenis sebesar 0,7129, indeks kekayaan jenis sebesar 2,1983, indeks dominasi spesies yaitu 0,2310. Kata kunci: Makroalga, Morfologi, Anatomi, Struktur komunitas, Meras